Effect of inhaled procaterol and budesonide on right ventricular diastolic function in children with asthma - Alit Utamayasa; Najib Advani; Imam Boediman; Sudigdo Sastroasmoro; Bambang Madiyono (Indonesian Pediatric Society Publishing House, 2009)
Objectives To study changes in parameters of right ventricular (RV) diastolic function after procaterol and budesonide inhalation in children with asthma. Methods This was a one-group pretest-posttest design to determine changes in right ventricular diastolic function following four weeks of inhaled procaterol and budesonide administration. Subjects were children aged 8 to 18 years with frequent episodic asthma recruited consecutively at the Department of Child Health, Cipto Mangunkusumo Hospital. M-mode and 2-D echocardiography examinations were performed to determine RV isovolumetric relaxation time (IVRT), acceleration time (AT), deceleration time (DT), E wave, A wave, E/ A ratio, and tricuspid annular plane systolic excursion (TAPSE). Means of the RV function parameters before and after treatment were compared using the paired t-test or Wilcoxon test. Results There were 29 patients comprising 16 boys and 13 girls. The means or medians of theE wave, A wave, E/A ratio, acceleration time (AT), deceleration time (DT), and isovolumetric relaxation time (IVRT) before and after treatment were 0.55 and 0.55 em/sec (P=0.709), 0.45 and 0.35 em/sec (P<O.OOOl), 1.17 and 1.58 em/sec (P<0.0001), 52.73 and 55.03 m/sec (P=0.04), 55.39 and 58.10 m/ sec (P=0.03), and 46.50 and 70.0 m/sec (P<0.0001), respectively. The median pre- and post-inhalation TAPSE were 1.63 and 1.84 em, respectively (P<0.001). Conclusions In children with frequent episodic asthma, there are changes in RV diastolic functions IVRT, AT, DT, E/A ratio and A wave following procaterol and budesonide inhalation. There was no increase in E wave following inhalation. TAPSE was increased following procaterol and budesonide inhalation.